Role of aqueous extract of morinda citrifolia (Indian noni) ripe fruits in inhibiting dental caries-causing streptococcus mutans and streptococcus mitis. - Barani Kumarasamy; Sunayana Manipal; Prabu Duraisamy; Adil Ahmed; Sp Mohanaganesh; C Jeevika (Tehran University of Medical Sciences, 2014)
Use of alternative medicine to control oral streptococci is a new topic worthy of further investigation. This study aimed to elucidate the dose-dependent anti-bacterial activity of crude aqueous extract of ripe Morinda citrifolia L. (Family: Rubiaceae) fruits against oral streptococci i.e. Streptococcus mutans and Streptococcus mitis, that cause dental caries in humans.Fresh ripe M. citrifolia fruits (750g) were ground in an electronic blender with sterile water (500ml). The crude aqueous extract was lyophilized to yield a brown colored powder. Various concentrations (1000-100μg/ ml) of the extract were tested for its antibacterial activity (Kirby and Bauer method) against whole cells of S. mutans and S. mitis. Minimum Inhibitory Concentration (MIC) was determined by micro-dilution method, using serially diluted (2 folds) fruit extract, according to the National Committee for Clinical Laboratory Standards (NCCLS).Crude aqueous extract (1000μg/ ml) of ripe M. citrifolia fruits effectively inhibited the growth of S. mutans (19±0.5 mm) and S. mitis (18.6±0.3 mm) compared to the streptomycin control (21.6±0.3 mm). The growth inhibition was clearly evident with "nil" bacteriostasis, even after 48 hours of incubation at 37°C. The MIC of the extract for S. mutans and S. mitis was 125 μg and 62.5 μg, respectively.Our results suggest that phytochemicals naturally synthesized by M. citrifolia have an inhibitory effect on oral streptococci. Furthermore, purification and molecular characterization of the "bioactive principle" would enable us to formulate a sustainable oral hygiene product.